Redesain Visual Identity Gofha Studio Parfume - Febri Ramadhani; Heldi Heldi (Universitas Negeri Padang, 2021)
Gofha studio Perfume is a business engaged in perfume refills in Payakumbuh. This business was founded by Taufik Hidayat on October 28, 2010. Gofha studio Parfume is located at Jl. Tan Malaka, Parik Muko Aie, Payakumbuh Lamposi Tigo Nagori, Payakumbuh City, West Sumatra 26219. Fundamental problems Business identity is not yet optimal, there is still no identity contained in the Gofha logo, and has not applied good and correct design principles. The purpose of this Visual Identity Redesign is to create a visual identity by implementing excellent design principles. therefore, it will give a strong identity and present a new face of the business that is expected to increase sales results in the future. The Glass Box approach, which is a rational thinking method, was employed as the analytical method, and the analysis used is SWOT. This design resulted in a Manual Book as the main media containing the Visual Identity Redesign designs starting from Thumbnails, Moodboards, concepts, grid systems, typography, colors. Supporting media is in the form of business cards, letters, stamps, posters, x-banners, T-shirts, paper bags, stickers, perfume bottles.Keywords: Redesign, Visual Identity, Gofha studio Parfume